Comparing Sensitivity and Specificity of Addenbrooke’s Cognitive Examination-I, III and Mini-Addenbrooke’s Cognitive Examination in Parkinson’s Disease - Tivadar Lucza; Zsuzsanna Ascherman; Márton Kovács; Attila Makkos; Márk Harmat; Annamária Juhász; József Janszky; Sámuel Komoly; Norbert Kovács; Krisztina Dorn; Kázmér Karádi (Behavioural Neurology)
Background. Parkinson’s disease (PD) is the second most common neurodegenerative disorder characterized by numerous motor and nonmotor symptoms. Neurocognitive disorders (NCD) are one of the most troublesome problems and their diagnosis is often challenging. Methods. We compared the sensitivity and specificity of several versions of Addenbrooke Cognitive Examination (ACE, ACE-III, and Mini-ACE) on 552 subjects with PD. Normal cognition, mild and major NCD were judged in accordance with the respective criteria of the Diagnostic and Statistical Manual of Mental Disorders 5th edition. Subsequently, we applied the receiver operation characteristic (ROC) analysis in comparison of different education levels. Results. For subjects with education level 0–8 and 9–12 years, the ACE-III had the best discriminating capabilities for mild NCD (cut-off scores: 83.5 and 85.5 points, respectively), while Mini-ACE was the best for subjects having education > 12 years (cut-off score: 25.5 points). For detecting major NCD, ACE-III had the best diagnostic accuracy in all levels of education (cut-off scores: 70.5, 77.5, and 78.5 points for subjects having education level 0–8, 9–12, and >12 years, respectively). Conclusion. ACE-III and its nested version, the Mini-ACE, had the best screening abilities for detecting mild and major NCD in PD.